Filmer les ruines et faire parler le présent : La Promesse de Franco de Marc Weymuller - Pascale Thibaudeau (Conserveries Mémorielles)
« Civil wars are memory wars. They seem endless » declares Marc Weymuller. In his documentary film Franco’s Promise (2014), he investigates the Spanish Civil War’s effects that endure today using the specific case of Belchite village, whose history and symbol have been widely and variously used for political purposes. This article focuses on the way the documentary film builds a reflexion about remembrance conflicts. It also questions the impact that its shooting and its reception had on the Belchite’s residents.